41 Use of clinic refractometer at farm, as a tool to estimate the IgG content in goat colostrum. (7th December 2018) - Castro, N; Arguello, A; Gomez-Gonzalez, L
Abstract: Refractometry has been proposed as a farm technique to estimate the IgG concentration in colostrum. In order to validate the method in goat colostrum using a clinical refractometer, 216 colostrum and milk samples were obtained from 54 dairy goats. Samples were evaluated for protein concentration using a clinical refractometer and IgG concentration was measure using a commercial ELISA. The r 2 for the linear regression between refractometry value and IgG concentration measured by ELISA was 0.79, and the area under the receiver operating characteristics curve was 0.99. The proposed cutoff value using the clinical refractometer was 10 mg/mL. At this point, the sensitivity, specificity, negative predictive value, positive predictive value, Youden index and accuracy were 100%, 95.19%, 100%, 76.32%, 0.95 and 95.83%.